OPTIMIZATION OF MICROSOFT OFFICE 365 FOR BLENDED LEARNING-BASED LEARNING IN NATURAL SCIENCE SUBJECTS - Isnanik Juni Fitriyah; Yayuk Mulyati; Indra Fardhani (JCER (Journal of Chemistry Education Research), 2021)
Abstract. Blended learning is one of the innovative learning models that integrates technology in line with the demands of learning in the 21st century and is relevant to learning in the pandemic era. Microsoft Office 365 is an office cloud application from Microsoft such as the desktop version of Microsoft Office that allows users to access e-mail, documents, contacts, calendars and collaborate anywhere and using various devices. This technology is one of the technologies that can help the learning process run with the Blended Learning model. The purpose of this study is to review the optimization of Microsoft Office 365 in Blended Learning-based learning. The type of research used is research with literature study method.